Polyploid Adipose Stem Cells Shift the Balance of IGF1/IGFBP2 to Promote the Growth of Breast Cancer - Fajka-Boja, Roberta; Szebeni, Gábor J.; Hunyadi-Gulyás, Éva; Puskás, László G.; Katona, Róbert L. (Frontiers in Oncology, 2020)
Background: The close proximity of adipose tissue and mammary epithelium predispose involvement of adipose cells in breast cancer development. Adipose-tissue stem cells (ASCs) contribute to tumor stroma and promote the growth of cancer cells. In our previous study, we have shown that murine ASCs, which undergo polyploidization during their prolonged in vitro culturing, enhanced the proliferation of 4T1 murine breast cancer cells in IGF1 dependent manner. Aims: In the present study, our aim was to clarify the regulation of ASC-derived IGF1. Methods: 4T1 murine breast carcinoma cells were co-transplanted with visceral fat-derived ASCs (vASC) or with the polyploid ASC.B6 cell line into female BALB/c mice and tumor growth and lung metastasis were monitored. The conditioned media of vASCs and ASC.B6 cells were subjected to LC-MS/MS analysis and the production of IGFBP2 was verified by Western blotting. The regulatory effect was examined by adding recombinant IGFBP2 to the co-culture of ASC.B6 and 4T1. Akt/protein kinase B (PKB) activation was detected by Western blotting. Results: Polyploid ASCs promoted tumor growth and metastasis more potently than vASCs with normal karyotype. vASCs produced the IGF1 regulator IGFBP2, which inhibited the proliferation of 4T1 cells. Downregulation of IGFBP2 by polyploidization of ASCs and enhanced secretion of IGF1 allowed survival signaling in 4T1 cells, leading to Akt phosphorylation. Conclusions: Our results implicate that ASCs in the tumor microenvironment actively regulate the growth of breast cancer cells through the IGF/IGFBP system.